Valorisation of egg shell ash as a potential replacement for lime in stabilization of expansive soils - James Jijo; Jothi Priya K.; Karthika P.; Kokila S.; Vidyasagar V. (Građevinski Materijali i Konstrukcije, 2020)
The investigation focussed on the possibility of replacing lime in soil stabilization using Egg Shell Ash (ESA), a waste derived from poultry industry. An expansive soil was characterized for its properties in the lab. The minimum lime content required for modification of soil properties was determined from the Eades and Grim pH test. This lime content came out to be 3%. The lime content was replaced using ESA in the proportions of 33%, 50%, 67% and 100%. Unconfined compression test specimens of dimension 38 mm x 76 mm were cast for different combinations and were cured for periods of 3, 7 and 28 days. Samples were also subjected to 1, 3 and 5 cycles of wetting and drying to understand its durability. After the designated curing periods and cycles of wetting and drying, they were strained axially till failure. Atterberg limits tests were done to determine the plasticity of the stabilized soil. The strength results indicated that ESA cannot be used under normal conditions as a replacement for lime, however, ESA replacement resulted in good durability of the specimens under conditions of wetting and drying. It was concluded that ESA replacement of lime can be adopted in conditions of wetting and drying.